KAJIAN ALAT MUSIK SILOTUANG DI DUSUN JAGOI KINDAU KECAMATAN JAGOI BABANG KABUPATEN BENGKAYANG - Ardiana, Ersie; Mering, Aloysius; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to describe the history of silotuang, describe silotuang organology, describe the music system of silotuang and the design of the lesson. Due to this importance, analytic descriptive method in form of qualitative under the approach of ethnomusicology was needed. The sources of the data were three interviewees and one validator with the technique of observation, interview, and documentation. The validity of the data was obtained through three types of tringualation, they were; source, technique, and time, with the technique of the anlysis of Spradley model. The result of this research was in 1985 Silotuang was considered traditional music instrument in Jagoi Dayaknese. Based on shape, Silotuang is still original it has not modificated yet. The basic material of Silotuang is Bamboo Toling Manah Basah. Silotuang is functioned as the to nurturing instrument in rituals of curing and Gawai. The conclusion of this research is Silotuang as origin music instrument of Jagoi Kindau exactly in 1985, which made from Toling Manah Basah and played by rhytmicKey Words: Silotuang, Music Art, Traditional Music Instrument